Faecalibacillus intestinalis gen. nov., sp. nov. and Faecalibacillus faecis sp. nov., isolated from human faeces. Issue 7 (17th May 2019) - Seo, Boram; Jeon, Kyungchan; Baek, Inwoo; Lee, Yung Mi; Baek, Kiwoon; Ko, GwangPyo
Abstract : Two long-rod-shaped, Gram-stain-positive, obligately anaerobic and non-spore-forming strains, SNUG30099 T and SNUG30370 T, were isolated from faecal samples of healthy Korean subjects. The strains formed circular ivory-coloured colonies on Brain-heart infusion medium supplemented with 0.5% Difco yeast extract (YBHI) agar and cells were approximately 3.5–4.5×0.3–0.4 µm in size. Taxonomic analyses based on 16S rRNA gene sequences distinguished the strains from other species within the family Erysipelotrichaceae . The closest relative of strains SNUG30099 T and SNUG30370 T was Longibaculum muris (92.9 % and 93.6 % similarity, respectively), followed by Clostridium saccharogumia (92.3 % and 92.2 %). Phylogenetic inference also divided the strains into a unique branch that differed from other related strains that belong to the family Erysipelotrichaceae . DNA G+C contents based on the whole genome sequences of strains SNUG30099 T and SNUG30370 T were 29.2 and 30.2 mol%, respectively. Both novel strains possessed meso -diaminopimelic acid as the peptidoglycan, and phosphatidylethanolamine was observed as one of the major polar lipids. The major cellular fatty acid composition was different from those of other related taxa. In addition, the profile of biochemical activities advocated that the strains have distinct characteristics in comparison to other strains. Taken together, a novel genus, named Faecalibacillus gen. nov., is proposed, which includes the type species Faecalibacillus intestinalis sp. nov. for strain SNUG30099 T and Faecalibacillus faecis sp. nov. for strain SNUG30370 T . The type strains of these novel species are SNUG30099 T (=KCTC 15631 T =JCM 32256 T ) and SNUG30370 T (=KCTC 15632 T =JCM 32257 T ).